بناء نموذج لتحديد البنوك ذات الأهمية النظامية محليا (d-sibs) على مستوى النظام المصرفي الجزائري - رقايقية فاطمة الزهراء; ناصري عبد الناصر (My University, 2021)
تهدف هذه الدراسة إلى تحديد البنوك ذات الأهمية النظامية محليا على مستوى النظام المصرفي الجزائري من خلال بناء نموذج (SCOREi) يعتمد على مخرجات التقارير المالية لسنة (2018) الصادرة عن البنوك العشرين المعتمدة في الجزائر. وخلصت الدراسة إلى ستة بنوك محلية ذات أهمية نظامية على مستوى النظام المصرفي الجزائري، حيث استحوذت البنوك العمومية الستة على قائمة(D-SIBs)، من خلال السيطرة على جميع المؤشرات المالية المكونة للنموذج بمعدلات كبيرة. Abstract: This study aims to determine the domestic systemically important banks (D-SIBs) in the Algerian banking system, by building a (SCOREi) model based on the balance sheet information issued on (2018) by twenty accredited banks in Algeria. The study has concluded that six domestic systemically important banks at the level of the Algerian banking system, as the public banks obtained the list of (D-SIBs), by controlling all the financial indicators that form the model by great rate